Identifikasi SWOT Dan Kualitas Pelayanan Dalam Meningkatkan Jumlah Nasabah BFI Syariah Pada PT. BFI Finance Indonesia - Juhardi Juhardi; Sutia Budi (ITB Ahmad Dahlan Jakarta, 2019)
The purpose of this study was to identify the strengths, weaknesses, opportunities, threats, and quality of service in increasing the number of customers BFI Syariah at PT. BFI Finance Indonesia Tbk. This research is a qualitative descriptive study. Data identified using SWOT analysis. These results indicate that; 1. Strength BFI Syariah namely: faster disbursement of funds in a matter of hours, the total disbursement of up to 90% of the value of the collateral, a weakness that is: complex filing requirements and details, which offered high interest, credit guarantee is limited to only focus on Islamic products, product marketing evenly distributed both online and offline, chances are: the increasing public demand for access to venture capital, the high number of people who have a dynamic lifestyle, the rampant activities of traveling, kosher and Umrah travel and threat namely: The emergence of finance companies as new competitors, the government's policy on lending rates, inflation value of the rupiah against foreign currencies. 2. For service quality index found to yield at 80.1% which is in the range from 0.76 to 1.00 (76% - 100%), which means the quality of service that consumers got very good. With good service quality is one of the keys to increasing the number of potential consumers BFI Sharia.